Species-Specific 5 mC and 5 hmC Genomic Landscapes Indicate Epigenetic Contribution to Human Brain Evolution - Madrid, Andy; Chopra, Pankaj; Alisch, Reid S. (Frontiers in Molecular Neuroscience, 2018)
Human evolution from non-human primates has seen substantial change in the central nervous system, with the molecular mechanisms underlying human brain evolution remaining largely unknown. Methylation of cytosine at the fifth carbon (5-methylcytosine; 5mC) is an essential epigenetic mark linked to neurodevelopment, as well as neurological disease. The emergence of another modified form of cytosine (5-hydroxymethylcytosine; 5hmC) that is enriched in the brain further substantiates a role for these epigenetic marks in neurodevelopment, yet little is known about the evolutionary importance of these marks in brain development. Here, human and monkey brain tissue were profiled, identifying 5,516 and 4,070 loci that were differentially methylated and hydroxymethylated, respectively, between the species. Annotation of these loci to the human genome revealed genes critical for the development of the nervous system and that are associated with intelligence and higher cognitive functioning, such as RELN and GNAS. Moreover, ontological analyses of these differentially methylated and hydroxymethylated genes revealed a significant enrichment of neuronal/immunological–related processes, including neurogenesis and axon development. Finally, the sequences flanking the differentially methylated/hydroxymethylated loci contained a significant enrichment of binding sites for neurodevelopmentally important transcription factors (e.g., OTX1 and PITX1), suggesting that DNA methylation may regulate gene expression by mediating transcription factor binding on these transcripts. Together, these data support dynamic species-specific epigenetic contributions in the evolution and development of the human brain from non-human primates.